A functional fiber separator, a preparation method thereof and its application in a polymer solid-state lithium battery

The polymer/inorganic salt composite fiber separator with built-in electronic conductor nanorod filler was prepared through electrospinning technology, which solved the problems of poor rate performance, low capacity and short cycle life of solid-state lithium batteries, achieved efficient lithium ion migration and stable deposition, and improved the battery's conductivity and cycle stability.

CN118315765BActive Publication Date: 2025-03-21HARBIN INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410438436.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-12
Publication Date
2025-03-21
Estimated Expiration
2044-04-12

AI Technical Summary

Technical Problem

The existing polymer solid-state lithium batteries have poor rate performance, low capacity and short cycle life, which are mainly due to the uneven dispersion of inorganic fillers in the electrolyte and the discontinuity of lithium ion migration network.

Method used

Electrospinning technology is used to prepare polymer/inorganic salt composite fiber membranes with built-in electronic conductor nanorod fillers, forming a three-dimensional framework through thermal microcrosslinking, optimizing the lithium ion migration network, and improving conductivity and cycling stability.

Benefits of technology

It realizes efficient migration and stable deposition of lithium ions, improves the room temperature conductivity and lithium ion migration of solid-state lithium batteries, extends the cycle life of the battery, and improves the long-term cycle stability of the negative electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118315765B_ABST
    Figure CN118315765B_ABST
Patent Text Reader

Abstract

A functional fiber diaphragm, a preparation method thereof and an application thereof in a polymer solid-state lithium battery, which relates to a fiber diaphragm and a preparation method and application thereof. It aims to solve the problems of poor rate performance, low capacity and short cycle life of polymer solid-state lithium batteries. The functional fiber diaphragm is formed by electrostatic spinning and thermal micro-crosslinking of a polymer / inorganic salt mixed solution dispersed with electronic conductor nanorod fillers. Preparation method: electrostatic spinning and calcining a mixed solution of metal salt and polymer powder to obtain an electronic conductor nanorod powder; then electrostatic spinning and thermal micro-crosslinking of the mixed solution with a polymer and an inorganic salt to obtain a functional fiber diaphragm; applying a polymer electrolyte precursor liquid on the fiber diaphragm and then polymerizing and curing to obtain a solid polymer electrolyte; assembling a positive electrode, a functional fiber diaphragm and a negative electrode into a solid-state lithium battery, the capacity retention rate of the battery after 800 cycles at room temperature is 76.1% to 82.3%, and can be used in the field of lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of solid-state lithium batteries, and specifically relates to a fiber diaphragm and a preparation method and application thereof. Background Art

[0002] Research and develop secondary battery systems with high specific energy, long life, and fast charge and discharge to meet the practical application needs of various scenarios and promote the development of new energy. The high electrochemical stability of solid electrolytes makes it possible to match lithium metal anodes with high-voltage layered transition metal oxide cathodes, which is expected to increase the energy density of batteries to 400Wh kg -1 The above results in a solid-state lithium battery technology that combines high energy density with high safety. However, due to the high reactivity of metallic lithium and the stripping conversion reaction characteristics without a matrix, the transition from graphite anode to lithium anode poses a severe challenge to solid-state batteries. In addition, the conductivity of solid polymer electrolytes is still not comparable to that of organic electrolytes, and the existence of concentration polarization accelerates the Li + The uneven deposition of carbon dioxide restricts the power density and cycle life of solid-state lithium batteries.

[0003] As an important component of solid-state lithium batteries, the microscopic morphology and composition structure of solid electrolytes directly determine the kinetic properties of ion transport and the stability of the electrode interface. Compared with the introduction of other polymers for blending and cross-linking, adding liquid plasticizers, etc., the introduction of inorganic fillers into polymer electrolytes can not only more effectively improve the conductivity and mechanical strength at the same time, but also enhance the compatibility of the positive and negative electrode interfaces of the electrolyte, and improve the long-term cycle stability of high-energy polymer solid-state lithium batteries. However, the commonly used active fillers of lithium ion conductors are still facing technical bottlenecks such as high production costs, harsh manufacturing environments, and easy generation of impurities on the surface; and due to the high surface energy of nanofillers, the organic-inorganic composite solid electrolyte obtained by two-phase physical blending and solution casting is very prone to filler agglomeration. The above factors have led to the fact that the improvement effect of existing inorganic fillers on the electrochemical properties of polymer electrolytes is not ideal. Among them, the slow lithium ion transport kinetics, the uneven ion beam distribution on the electrode surface, and the uncontrollable lithium dendrite growth have become the key problems that need to be solved behind them, limiting the long-life stable cycle of solid-state lithium batteries under fast charging and discharging conditions. Therefore, exploring other potential inorganic filler systems, designing new composite methods for uniform dispersion of fillers, and forming a bulk-interface high-speed lithium ion migration network are expected to fundamentally improve the rate characteristics and cycle stability of solid polymer electrolytes and promote the practical application of solid-state lithium metal batteries. Summary of the invention

[0004] The present invention aims to solve the technical problems of poor rate performance, low capacity and short cycle life of existing polymer solid-state lithium batteries, and to provide a functional fiber diaphragm, a preparation method thereof and its application in polymer solid-state lithium batteries.

[0005] The functional fiber diaphragm of the present invention is formed by electrostatic spinning and thermal micro-crosslinking of a polymer / inorganic salt mixed solution in which electronic conductor nanorod fillers are dispersed, wherein the mass of the electronic conductor nanorod fillers accounts for 5% to 15% of the mass of the polymer in the fiber diaphragm obtained by electrostatic spinning; the electronic conductor nanorod fillers are one or more of lanthanum cobaltate, strontium-doped lanthanum cobaltate, strontium and iron co-doped lanthanum cobaltate, lanthanum manganate, and strontium-doped lanthanum manganate.

[0006] Furthermore, the polymer in the fiber membrane obtained by electrospinning is one or more of polyimide and polyamic acid.

[0007] Furthermore, the inorganic salt in the fiber membrane obtained by electrospinning is one or more of zinc acetate, zinc nitrate, copper acetate and copper nitrate.

[0008] Furthermore, the mass of the inorganic salt in the fiber membrane obtained by electrospinning accounts for 10% to 15% of the mass of the polymer.

[0009] The preparation method of the fiber diaphragm is carried out according to the following steps:

[0010] 1. Preparation of electronic conductor nanorods:

[0011] (1) dissolving raw material I in N,N-dimethylformamide according to the stoichiometric ratio of the electronic conductor nanorods, stirring for 2 to 3 hours to obtain a mixed solution I; adding polyvinyl pyrrolidone to the mixed solution I, and continuing to stir for 6 to 8 hours to obtain an electrospinning solution I; wherein the electronic conductor nanorod filler is one or more of lanthanum cobaltate, strontium-doped lanthanum cobaltate, strontium and iron co-doped lanthanum cobaltate, lanthanum manganate, and strontium-doped lanthanum manganate; and the raw material I is one or more of lanthanum nitrate, strontium nitrate, cobalt nitrate, iron nitrate, and manganese acetate;

[0012] (2) extracting the electrospinning solution I into a 5 mL syringe, adjusting the distance between the receiver and the metal needle of the syringe to 10-20 cm, the DC voltage to 15-20 kV, the injection speed to 0.8-1.5 mL / h, the temperature to 40-50° C., and the ambient humidity to less than 35%, and performing electrospinning to obtain an electronic conductor precursor fiber;

[0013] (3) placing the electronic conductor precursor fiber in a box-type muffle furnace, heating it to 800-1000° C. at a heating rate of 2-3° C. / min, calcining it for 3-5 h, and then naturally cooling it to room temperature to obtain electronic conductor nanorod powder;

[0014] 2. Preparation of polymer / inorganic salt composite fiber diaphragm with built-in electronic conductor nanorod filler:

[0015] (1) dissolving the electronic conductor nanorod powder and raw material II in N,N-dimethylformamide, stirring for 2 to 3 hours to obtain a mixed solution II; dissolving the polymer I powder in the mixed solution II, heating and stirring for 6 to 8 hours to obtain an electrospinning solution II; the raw material II is one or more of zinc acetate, zinc nitrate, copper acetate and copper nitrate; the polymer I is one or more of polyimide and polyamic acid;

[0016] (2) extracting the electrospinning solution II into a 5 mL syringe, adjusting the distance between the receiver and the metal needle of the syringe to 10-20 cm, the DC voltage to 12-18 kV, and the injection speed to 0.5-1.0 mL / h, and performing electrospinning to obtain a polymer / inorganic salt composite fiber diaphragm with built-in electronic conductor nanorod filler;

[0017] 3. Preparation of polymer / metal oxide / metal nitride composite fiber diaphragm with built-in electronic conductor nanorod filler:

[0018] The polymer / inorganic salt composite fiber diaphragm with built-in electronic conductor nanorod filler is placed in a box-type muffle furnace, heated to 250°C at a heating rate of 2-3°C / min, and kept at a temperature for 1-2 hours. The temperature is then further heated to 340°C at a heating rate of 2-3°C / min, and kept at a temperature for 1-2 hours. The membrane is then naturally cooled to room temperature to obtain a polymer / metal oxide / metal nitride composite fiber diaphragm with built-in electronic conductor nanorod filler.

[0019] Furthermore, in step one (1), the mass ratio of raw material I to N,N-dimethylformamide in the electrospinning solution I is 1:(6-6.5).

[0020] Furthermore, in step one (1), the mass ratio of polyvinyl pyrrolidone to N,N-dimethylformamide in the electrospinning solution I is 1:(6.5-7).

[0021] Furthermore, in step 2 (1), the mass ratio of the electronic conductor nanorod powder to N,N-dimethylformamide in the electrospinning solution II is 1:(22-72).

[0022] Furthermore, in step 2 (1), the mass ratio of the electronic conductor nanorod powder to the polymer I powder in the electrospinning solution II is 1:(6.7-20).

[0023] Furthermore, in step 2 (1), the mass ratio of raw material II to polymer I powder in the electrospinning solution II is 1:(8.5-8.8).

[0024] Furthermore, the heating and stirring temperature in step 2 (1) is 60-80°C.

[0025] Furthermore, the thickness of the fiber membrane obtained in step three is 60-65 μm.

[0026] The application of the above-mentioned fiber diaphragm is to fill the fiber diaphragm with polymer electrolyte to prepare a solid polymer electrolyte film for use in solid-state lithium batteries; the filled polymer electrolyte is formed by solidifying lithium salt, polymer monomer, initiator, cross-linking agent and plasticizer through polymerization reaction; the mass of lithium salt accounts for 50% to 70% of the polymer monomer, the mass of initiator accounts for 0.5% to 3% of the polymer monomer, the mass of cross-linking agent accounts for 10 to 20% of the polymer monomer, and the mass of plasticizer accounts for 50% to 70% of the polymer monomer.

[0027] The method for preparing a solid polymer electrolyte using a fiber separator is carried out according to the following steps:

[0028] 1. Preparation of polymer electrolyte precursor solution: weigh lithium salt, polymer monomer, initiator, crosslinker and plasticizer; wherein the mass of lithium salt accounts for 50% to 70% of polymer monomer, the mass of initiator accounts for 0.5% to 3% of polymer monomer, the mass of crosslinker accounts for 10 to 20% of polymer monomer; the mass of plasticizer accounts for 50% to 70% of polymer monomer; first add lithium salt to polymer monomer, stir at room temperature for 1 to 2h, then add plasticizer, crosslinker and initiator, stir evenly at room temperature to obtain polymer electrolyte precursor solution;

[0029] 2. Preparation of solid polymer electrolyte: Place the fiber diaphragm in a glass container, evenly apply the polymer electrolyte precursor liquid on the fiber diaphragm, seal the glass container, heat and polymerize to obtain a solid polymer electrolyte.

[0030] Furthermore, the lithium salt described in step 1 is one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium hexafluorophosphate, lithium bis(oxalate)borate, lithium difluorooxalateborate, lithium perchlorate and lithium bis(fluorosulfonyl)imide;

[0031] Furthermore, the polymer monomer in step 1 is one or more of vinylene carbonate, dioxolane, methyl methacrylate, butyl acrylate, and triethylene glycol diacrylate;

[0032] Furthermore, the plasticizer in step 1 is one or more of fluoroethylene carbonate, triethyl phosphate, succinonitrile, propylene carbonate, dimethyl carbonate, diethyl carbonate, and trimethyl phosphate;

[0033] Furthermore, the cross-linking agent in step 1 is one or more of glycerol triglycidyl ether, polyethylene glycol diacrylate, polyethylene glycol monomethyl ether monomethacrylate, and polyethylene glycol dimethacrylate;

[0034] Furthermore, the initiator in step 1 is azobisisobutyronitrile or azobisisoheptanenitrile;

[0035] Furthermore, the scraping amount described in step 2 is 20 to 30 μL / cm 2 ;

[0036] Furthermore, the heating curing temperature in step 2 is 60 to 80° C., and the heating curing time is 2 to 10 hours;

[0037] Furthermore, the thickness of the solid polymer electrolyte prepared in step 2 is 120-130 μm;

[0038] The method for preparing a polymer solid-state lithium battery using a functional fiber separator is carried out according to the following steps:

[0039] 1. Preparation of polymer electrolyte precursor solution: weigh lithium salt, polymer monomer, initiator, crosslinker and plasticizer; wherein the mass of lithium salt accounts for 50% to 70% of polymer monomer, the mass of initiator accounts for 0.5% to 3% of polymer monomer, the mass of crosslinker accounts for 10 to 20% of polymer monomer; the mass of plasticizer accounts for 50% to 70% of polymer monomer; first add lithium salt to polymer monomer, stir at room temperature for 1 to 2h, then add plasticizer, crosslinker and initiator, stir evenly at room temperature to obtain polymer electrolyte precursor solution;

[0040] 2. Preparation of polymer solid-state lithium battery: Place the positive electrode, fiber diaphragm and negative electrode in the battery shell, inject the polymer electrolyte precursor solution between the fiber diaphragm and the electrode, and after the battery is packaged, place it in an oven for heating and curing to obtain an in-situ polymerized polymer solid-state lithium battery.

[0041] Furthermore, the positive electrode in step 2 is lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium cobalt oxide or lithium nickel cobalt aluminum oxide;

[0042] Furthermore, the negative electrode in step 2 is metallic lithium, graphite, lithium titanate or silicon oxide;

[0043] Furthermore, the heating curing temperature in step 2 is 60-80° C., and the heating curing time is 2-10 hours.

[0044] The present invention utilizes a thermally induced micro-crosslinked fiber diaphragm as a carrier of an electronic conductor nanorod filler, and fills it into a polymer electrolyte as a three-dimensional skeleton. Under the premise of avoiding the occurrence of electronic conduction penetration between the positive and negative electrodes, the original solvation structure of the polymer electrolyte can be optimized through the defective electronic environment on the surface of the filler, forming a migration model with higher lithium ion mobility and transmission efficiency, and combining the electrical response characteristics of the electronic conductor under the action of an external electric field, the formed built-in electric field can further accelerate the migration of lithium ions; when the polymer solid electrolyte prepared by the present invention is matched with the lithium metal negative electrode, the metal oxides and metal nitrides formed on the surface of the thermally induced micro-crosslinked fiber diaphragm, and through an in-situ electrochemical reduction reaction, the growth hotspots of lithium dendrites can be effectively eliminated, and the two-dimensional plane deposition of lithium can be promoted, and finally a solid-state lithium battery with high specific energy, fast charge and discharge, and long cycle life is obtained, which provides a new technology for promoting the practical process of solid-state batteries. The fiber diaphragm of the present invention can solve the technical bottlenecks such as low capacity, poor rate performance, and short cycle life of polymer solid-state lithium batteries, and provides the possibility of building high-performance solid-state batteries.

[0045] The beneficial effects of the present invention are as follows:

[0046] (1) The present invention provides a functional fiber diaphragm with built-in electronic conductor inorganic filler through the co-blending electrostatic spinning technology. The steric hindrance effect provided by the jet splitting under the action of the electric field for the fiber can not only ensure the independent and uniform dispersion of the electronic conductor filler inside the polymer fiber, avoiding its percolation interconnection and thus conducting the electron transmission between the positive and negative electrodes, but also can utilize the axial arrangement characteristics of the nanorod filler and the polymer fiber under the action of the electric field force to form a coaxial core-shell structure with the electronic conductor nanorod filler inside and the polymer fiber wrapped outside. This morphological advantage can promote the orderly arrangement of the lithium ion percolation transmission channel and provide a three-dimensional continuous ion transmission network for the solid polymer electrolyte. This method is particularly suitable for the electronic conductive LSC filler provided by the present invention, and provides an innovative new idea for its composite method.

[0047] (2) The fiber diaphragm provided by the present invention has an oxygen vacancy defect structure formed by low-valent ion doping and dipole concentration optimization, and the metal atoms around the oxygen vacancies on the surface of the crystal can interact with TFSI in the polymer electrolyte. - The anions produce a stronger degree of charge transfer, forming a more stable adsorption configuration, while weakening the coordination effect of the polymer polar groups on lithium ions, forming a solvation configuration with higher lithium ion mobility. Under the action of an external electric field, the dielectric properties of the electronic conductor cause a directional charge transfer from oxygen atoms to adjacent metal atoms around the oxygen vacancy defects inside the crystal. The resulting built-in electric field further accelerates the lithium ion transfer kinetics, increasing the room temperature conductivity of the solid polymer electrolyte to 1.50×10-3 S / cm, and the lithium ion migration number is increased to 0.91.

[0048] (3) The fiber membrane provided by the present invention can be used as a three-dimensional skeleton in the solid polymer electrolyte. The metal oxide / metal nitride components on its surface can be used to react with the dendrite-shaped lithium metal in direct contact with its surface to form an interface film that is beneficial to the kinetics of lithium metal deposition reaction. At the same time, the growth of lithium dendrites can be eliminated and the microscopic electrodeposition behavior of lithium metal can be regulated, thereby improving the long-term cycle stability of the negative electrode. The polymer solid-state lithium||lithium symmetric battery based on the fiber membrane of the present invention has a high cycle stability of 0.2 mA cm -2 and 0.2 mAh cm -2 Under the same conditions, it has a cycle stability of 1200 hours and a limiting current density of 1.7 mA cm -2 The polymer solid-state lithium||lithium iron phosphate battery based on the fiber diaphragm of the present invention exhibits high cycle reversibility. The maximum discharge capacity of room temperature cycle at 5C rate can reach 117.0mAh / g, and the capacity retention rate after 300 cycles is 95.1%; the first cycle discharge capacity of room temperature cycle at 2C rate is 144.6mAh / g, and the capacity retention rate after 500 cycles is 78.8%; the first cycle discharge capacity of room temperature cycle at 1C rate is 162.3mAh / g, and the capacity retention rate after 800 cycles is 82.3%; the first cycle discharge capacity of room temperature cycle at 0.5C rate is 153.3mAh / g, and the capacity retention rate after 1500 cycles is 61.0%; the polymer solid-state lithium||lithium nickel cobalt manganese oxide (LiNi 0.5 Co 0.2 Mn 0.3 O2) battery exhibits high cycle reversibility, with a first cycle discharge capacity of 178.3 mAh / g at room temperature at a rate of 1C, and a capacity retention rate of 73.2% after 300 cycles; the polymer solid lithium||nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 The O2) battery exhibits high cycle reversibility. The first cycle discharge specific capacity at room temperature under 0.5C rate is 176.6 mAh / g, and the capacity retention rate after 150 cycles is 84.8%. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 is a scanning electron microscope image of the strontium-doped lanthanum cobaltate nanorods prepared in Example 1.

[0050] Figure 2 3 is a transmission electron microscope image of the strontium-doped lanthanum cobaltate nanorods prepared in Example 1.

[0051] Figure 3 This is the X-ray diffraction spectrum of the strontium-doped lanthanum cobaltate nanorods prepared in Example 1.

[0052] Figure 4 This is the X-ray photoelectron spectrum of the strontium-doped lanthanum cobaltate nanorods prepared in Example 1.

[0053] Figure 5 This is a scanning electron microscope image of the polyimide / zinc acetate composite fiber diaphragm with built-in strontium-doped lanthanum cobaltate nanorod filler prepared in Example 1.

[0054] Figure 6 This is a scanning electron microscope image of the polyimide / zinc oxide / zinc nitride composite fiber diaphragm with built-in strontium-doped lanthanum cobaltate nanorod filler prepared in Example 1.

[0055] Figure 7 This is a Fourier transform infrared spectrum of the polyimide / zinc acetate with built-in strontium-doped lanthanum cobaltate nanorod filler prepared in Example 1.

[0056] Figure 8 This is a Fourier transform infrared spectrum of the polyimide / zinc oxide / zinc nitride composite fiber diaphragm with built-in strontium-doped lanthanum cobalt oxide nanorod filler prepared in Example 1.

[0057] Fig. 9 This is an X-ray photoelectron spectrum of the polyimide / zinc oxide / zinc nitride composite fiber diaphragm with built-in strontium-doped lanthanum cobaltate nanorod filler prepared in Example 1.

[0058] Fig.10 This is a scanning electron microscope image of the polymer solid electrolyte prepared using the composite fiber membrane as a three-dimensional skeleton in Example 1.

[0059] Fig.11 This is the AC impedance spectrum of the polymer solid electrolyte prepared with the composite fiber membrane as the three-dimensional skeleton in Example 1.

[0060] Fig.12 This is a DC polarization curve of the polymer solid electrolyte prepared using the composite fiber membrane as a three-dimensional skeleton in Example 1.

[0061] Fig.13 It is a test curve of the lithium ion migration number of the polymer solid electrolyte prepared with the composite fiber membrane as the three-dimensional skeleton in Example 1, and the inner figure is the AC impedance spectrum before and after the migration number test.

[0062] Fig.14 This is a cycle curve diagram of the lithium||lithium symmetric battery based on polymer solid electrolyte in Example 1.

[0063] Fig.15This is a limiting current test curve of the lithium||lithium symmetric battery based on polymer solid electrolyte in Example 1.

[0064] Fig.16 5C cycle performance and voltage curve of the lithium||lithium iron phosphate solid-state lithium battery based on polymer solid electrolyte in Example 1.

[0065] Fig.17 2C cycle performance and voltage curve of the lithium||lithium iron phosphate solid-state lithium battery based on polymer solid electrolyte in Example 1.

[0066] Fig.18 This is a 1C cycle performance diagram of the lithium||lithium iron phosphate solid-state lithium battery based on polymer solid electrolyte in Example 1.

[0067] Fig.19 This is a 0.5C cycle performance diagram of the lithium||lithium iron phosphate solid-state lithium battery based on polymer solid electrolyte in Example 1.

[0068] Fig. 20 The lithium||lithium nickel cobalt manganese oxide (LiNi 0.5 Co 0.2 Mn 0.3 O2) 1C cycle performance and voltage curve of solid-state lithium battery.

[0069] Fig.21 The lithium||lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2) 0.5C cycle performance and voltage curve of solid-state lithium battery. DETAILED DESCRIPTION

[0070] The beneficial effects of the present invention are verified by the following examples.

[0071] Embodiment 1: The preparation method of the fiber diaphragm of this embodiment is carried out according to the following steps:

[0072] 1. Preparation of electronic conductor nanorod fillers:

[0073] (1) Weigh 38 g of N,N-dimethylformamide, add 2.39 g of lanthanum nitrate, 2.68 g of cobalt nitrate and 0.78 g of strontium nitrate, and continue stirring for 3 h to obtain a mixed solution; add 5.5 g of polyvinyl pyrrolidone to the mixed solution, and continue stirring for 6 h to obtain an electrospinning solution;

[0074] (2) extracting the electrospinning solution into a 5 mL syringe, adjusting the distance between the receiver and the metal needle of the syringe to 17 cm, the DC voltage to 20 kV, the injection speed to 1.0 mL / h, the temperature to 45° C., the ambient humidity to 30%, and performing electrospinning to obtain an electronic conductor precursor fiber;

[0075] (3) placing the electronic conductor precursor fiber in a box-type muffle furnace, heating the temperature to 900° C. at a heating rate of 3° C. / min in an air atmosphere for calcination for 5 h, and then naturally cooling to room temperature to obtain strontium-doped lanthanum cobalt oxide nanorod powder;

[0076] 2. Preparation of polymer / inorganic salt composite fiber diaphragm with built-in electronic conductor nanorod filler:

[0077] (1) Weighing 0.39 g of strontium-doped lanthanum cobalt oxide nanorod powder and 0.4 g of zinc acetate, dissolving them in 12.5 g of N,N-dimethylformamide, and stirring for 3 h to obtain a mixed solution; weighing 3.5 g of polyimide powder, dissolving it in the mixed solution, and stirring at 60° C. for 8 h to obtain an electrospinning solution;

[0078] (2) extracting the electrospinning solution into a 5 mL syringe, adjusting the distance between the receiver and the metal needle of the syringe to 17 cm, the DC voltage to 17 kV, and the injection speed to 0.6 mL / h, and performing electrospinning to obtain a polymer / inorganic salt composite fiber diaphragm with built-in electronic conductor nanorod filler;

[0079] 3. Preparation of polymer / metal oxide / metal nitride composite fiber diaphragm with built-in electronic conductor nanorod filler:

[0080] The polymer / inorganic salt composite fiber diaphragm with built-in electronic conductor nanorod filler prepared in step 2 is placed in a box-type muffle furnace, heated to 250°C at a heating rate of 3°C / min, kept warm for 1 hour, and then heated to 340°C at a heating rate of 3°C / min, kept warm for 1 hour, and then naturally cooled to room temperature to obtain a polymer / metal oxide / metal nitride composite fiber diaphragm with built-in electronic conductor nanorod filler.

[0081] Figure 1 This is a scanning electron microscope image of the strontium-doped lanthanum cobalt oxide nanorod powder prepared in step 1 of Example 1. It can be seen that the strontium-doped lanthanum cobalt oxide material prepared by the electrospinning and high-temperature calcination process has a one-dimensional nanorod-like microscopic morphology, and the nanorod is composed of continuously grown nanocrystals.

[0082] Figure 2This is a transmission electron micrograph of the strontium-doped lanthanum cobalt oxide nanorod powder prepared in step 1 of Example 1. It can be seen that La, Sr and O elements are evenly distributed in the nanorods, and the lattice fringes with a spacing of 0.281 nm correspond to the (110) crystal plane of the cubic phase and perovskite structure lanthanum cobalt oxide.

[0083] Figure 3 This is the X-ray diffraction spectrum of the strontium-doped lanthanum cobalt oxide nanorod powder prepared in step 1 of Example 1. It can be seen that the diffraction peaks at diffraction angles of 23.2, 33.0, 40.7 and 47.4° can correspond to the (100), (110), (111) and (200) crystal planes of the cubic phase and perovskite structure lanthanum cobalt oxide.

[0084] Figure 4 This is the X-ray photoelectron spectrum of the strontium-doped lanthanum cobalt oxide nanorod powder prepared in step 1 of Example 1. It can be seen that the cobalt ions in the strontium-doped lanthanum cobalt oxide crystals are composed of trivalent and tetravalent cobalt ions. The signal peaks at the binding energies of 779.7 eV and 794.8 eV represent the Co 4+ , the signal peaks at 781.1eV and 796.1eV represent Co 3+ ,Co 4+ / Co 3+ The peak area ratio of the two valence ions is 1.49, indicating that the strontium-doped lanthanum cobalt oxide filler prepared in this embodiment has a strong electron transfer ability. It can also be seen that the signal peaks at the binding energies of 528.1eV, 529.1eV, 530.7eV, 531.8eV and 533.2eV correspond to the surface Sr-O bonds, the metal-oxygen bonds inside the strontium-doped lanthanum cobalt oxide lattice, oxygen vacancies, adsorbed oxygen species and adsorbed water molecules, respectively, indicating that the strontium-doped lanthanum cobalt oxide nanorods prepared in this embodiment form a rich surface oxygen vacancy structure.

[0085] Figure 5 This is a scanning electron microscope image of the polyimide / zinc acetate composite fiber diaphragm with built-in strontium-doped lanthanum cobalt oxide nanorod filler prepared in step 2 of Example 1. It can be seen that the strontium-doped lanthanum cobalt oxide nanorods are wrapped inside the polyimide / inorganic salt composite nanofibers, and the two show a one-dimensional axial arrangement characteristic, and the strontium-doped lanthanum cobalt oxide nanorods are distributed in a dispersed manner in the polyimide / inorganic salt composite nanofibers.

[0086] Figure 6This is a scanning electron microscope image of the polyimide / zinc oxide / zinc nitride composite fiber diaphragm with built-in strontium-doped lanthanum cobaltate nanorod filler prepared in step three of Example 1. It can be seen that the strontium-doped lanthanum cobaltate nanorods are wrapped inside the polyimide / zinc oxide / zinc nitride composite fiber, and the two show a one-dimensional axial arrangement characteristic. The strontium-doped lanthanum cobaltate nanorods show a dispersed distribution in the polyimide / zinc oxide / zinc nitride composite fiber; during the thermal micro-crosslinking treatment of the polyimide fiber and the oxidative decomposition of zinc acetate, the adjacent fibers melt and form crosslinking sites at the fiber overlap; and this unique coaxial core-shell structure will not be destroyed, and the morphology of the nanorods of the strontium-doped lanthanum cobaltate filler will not change. It can be seen from the cross-sectional scanning electron microscope image that the thickness of the fiber diaphragm is 65μm.

[0087] Figure 7 This is a Fourier transform infrared spectrum of the polyimide / zinc acetate composite fiber diaphragm with built-in strontium-doped lanthanum cobalt oxide nanorod filler prepared in step 2 of Example 1. Figure 8 This is the Fourier transform infrared spectrum of the polyimide / zinc oxide / zinc nitride composite fiber diaphragm with built-in strontium-doped lanthanum cobalt oxide nanorod filler prepared in step 3 of Example 1. By comparing the infrared spectra in the two figures, it can be seen that in the polyimide / zinc acetate composite fiber diaphragm with built-in strontium-doped lanthanum cobalt oxide nanorod filler, the -1 The vibration peaks at 1598 and 720 cm-1 represent the asymmetric and symmetric stretching vibrations of C=O. -1 The vibration peaks at 2960 and 1674 cm represent the trans and bending vibrations of C=O. -1 The vibration peak at 1372 cm represents the stretching and bending vibration of NH. -1 The vibration peak at the position is related to the stretching vibration of the CN bond. After the thermal micro-crosslinking treatment, the vibration peak related to the C=O bond was blue-shifted, and the vibration peak related to the NH and CN bonds was red-shifted, which indicates that the thermal melting of the polyimide molecules during the heat treatment caused the adjacent polyimide nanofibers to have intermolecular interactions and form a dense cross-linked structure. It can also be seen that in the polyimide / zinc oxide / zinc nitride composite fiber with built-in strontium-doped lanthanum cobalt oxide nanorod filler, the 453cm -1 and 427cm -1 Stretching vibration peaks representing Zn-O and Zn-N bonds appeared at the positions, indicating that zinc acetate underwent oxidative decomposition during the heat treatment and reacted with polyimide fibers to generate ZnO and Zn3N2 components.

[0088] Fig. 9This is the X-ray photoelectron spectrum of the polyimide / zinc oxide / zinc nitride composite fiber diaphragm with built-in strontium-doped lanthanum cobalt oxide nanorod filler prepared in step 3 of Example 1. It can be seen that in the spectrum of the C1s orbital, signal peaks at 283.7eV, 284.4eV, 285.3eV, 287.4eV and 289.3eV were detected, corresponding to the unsaturated carbon of the benzene ring, saturated CH / CC, benzene ring CN, O=CN and C=O on the polyimide segment. In the spectrum of the N1s orbital, in addition to the peaks at 399.2eV and 399.8eV representing O=CN and benzene ring CN, a peak at 397.8eV was also detected, corresponding to the Zn-N bond of Zn3N2. In the spectrum of O1s orbital, C=O (530.7 eV), surface adsorbed -OH (531.8 eV), and Zn-O bond (530.0 eV) in ZnO lattice were detected. In the spectrum of Zn 2p orbital, the peaks at 1020.7 / 1043.8 eV and 1020.3 / 1043.4 eV were attributed to Zn-O and Zn-N bonds. The above information shows that step 3 in Example 1 successfully synthesized ZnO and Zn3N2 components on the surface of polyimide fiber.

[0089] The method for preparing a solid polymer electrolyte using the fiber separator prepared in Example 1 is carried out according to the following steps:

[0090] 1. Preparation of polymer electrolyte precursor solution: Weigh 0.6 g of lithium bis(trifluoromethanesulfonyl)imide, add it to 1 mL of vinylene carbonate monomer, stir at room temperature for 2 h, then add 600 μL of fluoroethylene carbonate, 150 μL of propylene triglycidyl ether and 20 mg of azobisisobutyronitrile, stir evenly at room temperature to obtain a polymer electrolyte precursor solution;

[0091] 2. Preparation of solid polymer electrolyte: The polyimide / zinc oxide / zinc nitride composite fiber diaphragm with built-in strontium-doped lanthanum cobalt oxide nanorod filler prepared in Example 1 was placed in a glass container, and the polymer electrolyte precursor solution was evenly scraped on the fiber diaphragm, and the scraping amount was controlled to 25 μL / cm 2 The glass vessel was then sealed and heated at 70°C for 4 hours to obtain a solid polymer electrolyte.

[0092] Fig.10 This is a scanning electron microscope image of the polymer solid electrolyte prepared with the composite fiber membrane as the three-dimensional skeleton in Example 1. It can be seen that the polymer electrolyte after in-situ curing can produce good interface contact with the fiber skeleton to form an integrated solid polymer electrolyte film. It can be seen from the cross-sectional scanning electron microscope image that the thickness of the solid polymer electrolyte film is 130μm.

[0093] The solid polymer electrolyte prepared in Example 1 was used, and a stainless steel sheet was used as an ion blocking electrode to assemble a symmetrical cell of a stainless steel sheet|electrolyte|stainless steel sheet structure. The conductivity of the solid polymer electrolyte prepared in Example 1 was measured by electrochemical impedance spectroscopy using a CHI760 e electrochemical workstation. The test process and conditions were as follows:

[0094] The AC impedance test was performed at 10 6 The AC impedance test results were fitted by ZView software in the frequency range of 0.1 Hz to 0.1 Hz, with an amplitude of 5 mV and at room temperature. The ionic conductivity of the polymer electrolyte was calculated using the conductivity formula:

[0095] σ = d / RS (1)

[0096] In formula (1), σ represents the conductivity of the electrolyte, d represents the thickness of the electrolyte, R represents the bulk impedance of the fitted electrolyte, and S represents the effective contact area between the stainless steel sheet and the electrolyte.

[0097] Fig.11 1 is the AC impedance spectrum of the polymer solid electrolyte prepared with the composite fiber membrane as the three-dimensional skeleton in Example 1, and Table 1 is the conductivity of the solid polymer electrolyte.

[0098] Table 1 Conductivity of solid polymer electrolytes

[0099]

[0100] Based on the average value of the conductivity values ​​obtained from the four parallel samples, the solid polymer electrolyte prepared in Example 1 has a conductivity of 1.50×10 -3 The ionic conductivity of S / cm meets the practical standards of solid-state lithium batteries.

[0101] The solid polymer electrolyte prepared in Example 1 was used to assemble a symmetrical cell with a stainless steel sheet|electrolyte|stainless steel sheet structure. The electronic conductivity of the solid polymer electrolyte prepared in Example 1 was measured by a DC polarization test using a CHI760 e electrochemical workstation. The test process and conditions were as follows:

[0102] The DC polarization test was conducted at room temperature with a polarization voltage of 0.1 V, and the trend of the current over time was recorded. The electronic conductivity of the polymer electrolyte was calculated using the electronic conductivity formula:

[0103] σ = Id / US (2)

[0104] In formula (2), σ represents the electronic conductivity of the electrolyte, d represents the thickness of the electrolyte, I represents the steady-state current of the symmetrical battery, and S represents the effective contact area between the stainless steel sheet and the electrolyte.

[0105] Fig.12 The DC polarization curve of the polymer solid electrolyte prepared with the composite fiber membrane as the three-dimensional skeleton in Example 1. Calculation shows that the solid polymer electrolyte prepared in Example 1 has a DC polarization curve of 3.73×10 -10 The electronic conductivity of S / cm will not cause battery short circuit and meets the practical standards of solid-state lithium batteries.

[0106] The solid polymer electrolyte prepared in Example 1 was used to assemble a Li|electrolyte|Li symmetric battery. The lithium ion migration number of the electrolyte prepared in Example 1 was measured by a CHI760e electrochemical workstation using a DC polarization method and an AC impedance method. The test process and conditions were as follows:

[0107] In the DC polarization test, the applied polarization voltage is 10mV, and the current variation curve over time is recorded. The AC impedance method is used to test the interface impedance value of the Li|electrolyte|Li symmetric battery before and after polarization. The AC impedance test is carried out at 10 6 The frequency range is 0.1 Hz to 0.1 Hz, the amplitude is 5 mV, and the results of the AC impedance test are fitted by ZView software. The lithium ion migration number of the electrolyte is calculated according to the formula:

[0108] t Li+ = [I ss × (ΔV - I o R o )] / [I o × (ΔV - I ss R ss )] (3)

[0109] In formula (3), I o is the initial current value, I ss is the steady-state current value, R o Represents the interface impedance value at the initial state, R ss represents the interfacial impedance value in the stable state, and ΔV is the polarization voltage.

[0110] Fig.13 The graph is a test curve of the lithium ion migration number of the polymer solid electrolyte prepared with the composite fiber diaphragm as the three-dimensional skeleton in Example 1, and the built-in graph is the AC impedance spectrum before and after the migration number test. With the increase of polarization time, the current value gradually decreases from the initial 0.02403mA, and finally maintains at a steady-state value of 0.02144mA. The impedance fitting results before and after polarization show that the interface impedance of the lithium symmetric battery in the initial state and the stable state are 351.3Ω and 395.4Ω respectively. It is calculated that the solid polymer electrolyte has a lithium ion migration number of 0.91.

[0111] The solid polymer electrolyte prepared in Example 1 was assembled into a Li|electrolyte|Li symmetric battery, and a long-term cycle experiment was carried out. Constant capacity cycling was performed at a constant current density using a NEWARE CT-4008T multi-channel battery tester. The test temperature was room temperature to determine the lithium negative electrode interface stability of the electrolyte. Fig.14 : is a cycle curve diagram of the lithium||lithium symmetric battery based on the polymer solid electrolyte in Example 1. The lithium symmetric battery assembled based on the solid polymer electrolyte in Example 1, after 10 activation stages with a small current density, is then activated at a current density of 0.2 mA cm -2 , lithium deposition / deposition capacity is 0.2 mAh cm -2 Under actual conditions, it shows a low cycle overpotential, the voltage response value can remain stable for a long time during the 1200-hour test, and the symmetrical battery does not short-circuit during the cycle, indicating that the solid polymer electrolyte prepared in this embodiment has a high electrochemical stability at the lithium negative electrode interface.

[0112] The solid polymer electrolyte prepared in Example 1 was assembled into a Li|electrolyte|Li symmetric battery, and the limiting current density test was performed. The charge and discharge cycle test at different current densities was performed by a NEWARE CT-4008T multi-channel battery tester to determine the electrolyte's ability to resist lithium dendrite penetration. During the test, the charging and discharging time at each current density was fixed at 1 hour, and the current density started at 0.1 mA cm -2 The current density was tested in a step-wise manner (increase of 0.1 mA cm -2 ) until the battery short-circuits. Fig.15 : is a limiting current test curve of the lithium||lithium symmetric battery based on the polymer solid electrolyte in Example 1. It can be seen that the Li||Li symmetric battery based on the solid polymer electrolyte in Example 1 has a current density of 1.3 mA cm -2 Previously, the overpotential values ​​all showed a linear increase with the increase of current; when the current density was 1.3-1.6 mA cm -2 In this range, the symmetric battery can maintain stable cycling at a similar overpotential, indicating that only a soft short circuit occurred in the battery during this period, and the lithium dendrites did not completely penetrate the electrolyte. When the current density continued to rise to 1.7 mA cm -2 When the voltage response drops sharply, it indicates that the battery has a hard short circuit phenomenon and the lithium dendrites have completely penetrated the electrolyte. Therefore, the solid polymer electrolyte prepared in Example 1 has a current of 1.7 mA cm -2 The limiting current density value meets the practical standards of solid-state lithium batteries.

[0113] The fiber diaphragm prepared in Example 1 is used to prepare a polymer solid-state lithium battery. The specific preparation method is carried out according to the following steps:

[0114] 1. Preparation of polymer electrolyte precursor solution: Weigh 0.6 g of lithium bis(trifluoromethanesulfonyl)imide, add it to 1 mL of vinylene carbonate monomer, stir at room temperature for 2 h, then add 600 μL of fluoroethylene carbonate, 150 μL of propylene triglycidyl ether and 20 mg of azobisisobutyronitrile, stir evenly at room temperature to obtain a polymer electrolyte precursor solution;

[0115] 2. Preparation of polymer solid-state lithium battery: stack a disc-shaped lithium iron phosphate positive electrode with a diameter of 12mm, a fiber diaphragm disc with a diameter of 16mm, and a disc-shaped metal lithium negative electrode with a diameter of 15.6mm in order in the battery shell, inject the polymer electrolyte precursor solution between the fiber diaphragm and the electrode, the injection amount is 50μL, and after the precursor solution fully infiltrates the fiber diaphragm and the porous electrode, the battery shell is packaged, and the packaged battery is placed in an oven at 70℃ for heating and curing for 4h to obtain an in-situ polymerized polymer solid-state lithium battery.

[0116] The lithium||lithium iron phosphate polymer solid-state lithium battery prepared by using polyimide / zinc oxide / zinc nitride composite fiber separator with built-in strontium-doped lanthanum cobalt oxide nanorod filler was subjected to constant current charge and discharge cycle test (1C=170mAh / g) in the voltage range of 2.5~3.8V by NEWARE CT-4008T multi-channel battery tester. The test temperature was room temperature (25℃). The 5C cycle performance and voltage curve of the solid-state lithium battery are shown in the figure. Fig.16 As shown. It can be seen that the maximum discharge capacity of lithium||lithium iron phosphate polymer solid-state lithium battery can reach 117.0mAh / g at room temperature under 5C rate, the capacity retention rate after 300 cycles is 95.1%, and the average coulomb efficiency per cycle is 99.8%, which has excellent high-rate cycle stability; 2C cycle performance and voltage curve are shown in Fig.17 As shown in the figure, the first cycle discharge specific capacity of the lithium||lithium iron phosphate polymer solid-state lithium battery at room temperature under 2C rate is 144.6mAh / g, and the capacity retention rate after 500 cycles is 78.8%. It has a relatively stable charge and discharge voltage platform during the cycle process, and the charge and discharge polarization overpotential can remain stable during long-term cycling. Fig.18 The figure shows the long-term cycle performance of lithium||lithium iron phosphate polymer solid-state lithium battery at 1C rate. The first cycle discharge capacity of the battery is 162.3mAh / g, and the capacity retention rate after 800 cycles is 82.3%, which has excellent cycle stability. The long-term cycle performance at 0.5C is shown in Fig.19 As shown, it can be seen that the first cycle discharge specific capacity of the lithium||lithium iron phosphate polymer solid-state lithium battery at a rate of 0.5C is 153.3mAh / g, and the capacity retention rate after 1500 cycles is 61.0%.

[0117] The fiber diaphragm prepared in Example 1 is used to prepare a polymer solid-state lithium battery. The specific preparation method is carried out according to the following steps:

[0118] 1. Preparation of polymer electrolyte precursor solution: Weigh 0.6 g of lithium bis(trifluoromethanesulfonyl)imide, add it to 1 mL of vinylene carbonate monomer, stir at room temperature for 2 h, then add 600 μL of fluoroethylene carbonate, 150 μL of propylene triglycidyl ether and 20 mg of azobisisobutyronitrile, stir evenly at room temperature to obtain a polymer electrolyte precursor solution;

[0119] 2. Preparation of polymer solid-state lithium battery: stack a disc-shaped nickel cobalt manganese oxide positive electrode with a diameter of 12 mm, a fiber diaphragm disc with a diameter of 16 mm, and a disc-shaped metal lithium negative electrode with a diameter of 15.6 mm in the battery shell in order, inject the polymer electrolyte precursor solution between the fiber diaphragm and the electrode, the injection amount is 50 μL, and after the precursor solution fully infiltrates the fiber diaphragm and the porous electrode, the battery shell is packaged, and the packaged battery is placed in an oven at 70°C for heating and curing for 4 hours to obtain an in-situ polymerized polymer solid-state lithium battery.

[0120] Lithium||nickel cobalt manganese oxide (LiNi) prepared by using polyimide / zinc oxide / zinc nitride composite fiber separator with built-in strontium-doped lanthanum cobalt oxide nanorod filler 1-x-y Co x Mn y O2) polymer solid-state lithium battery, constant current charge and discharge cycle test in the voltage range of 2.8~4.3V by NEWARE CT-4008T multi-channel battery tester (LiNi 0.5 Co 0.2 Mn 0.3 1C of O2 material = 165mAh / g, LiNi 0.8 Co 0.1 Mn 0.1 O2 material 1C = 200mAh / g), the test temperature is room temperature (25℃). Fig. 20 It can be seen that the polymer solid lithium||lithium nickel cobalt manganese oxide (LiNi 0.5 Co 0.2 Mn 0.3 O2) battery exhibits high cycle reversibility, with a first cycle discharge capacity of 178.3 mAh / g at room temperature at a rate of 1C, and a capacity retention rate of 73.2% after 300 cycles; the polymer solid lithium||nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2) batteries show high cycle reversibility, and the 0.5C cycle performance and voltage curve are as follows Fig.21 As shown, the first cycle discharge specific capacity of room temperature cycling at 0.5C rate is 176.6 mAh / g, and the capacity retention rate after 150 cycles is 84.8%, indicating that the solid-state lithium battery prepared in this embodiment has excellent high voltage stability.

Claims

1. A method for preparing a functional fiber diaphragm, characterized in that: The method proceeds as follows:

1. Preparation of electronic conductor nanorods: (1) dissolving raw material I in N,N-dimethylformamide according to the stoichiometric ratio of the electronic conductor nanorods, stirring for 2 to 3 hours to obtain a mixed solution I; adding polyvinyl pyrrolidone to the mixed solution I, and continuing to stir for 6 to 8 hours to obtain an electrospinning solution I; wherein the electronic conductor nanorod filler is one or more of lanthanum cobaltate, strontium-doped lanthanum cobaltate, strontium and iron co-doped lanthanum cobaltate, lanthanum manganate, and strontium-doped lanthanum manganate; and the raw material I is one or more of lanthanum nitrate, strontium nitrate, cobalt nitrate, iron nitrate, and manganese acetate; (2) extracting the electrospinning solution I into a 5 mL syringe, adjusting the distance between the receiver and the metal needle of the syringe to 10-20 cm, the DC voltage to 15-20 kV, the injection speed to 0.8-1.5 mL / h, the temperature to 40-50° C., and the ambient humidity to less than 35%, and performing electrospinning to obtain an electronic conductor precursor fiber; (3) placing the electronic conductor precursor fiber in a box-type muffle furnace, heating it to 800-1000° C. at a heating rate of 2-3° C. / min, calcining it for 3-5 h, and then naturally cooling it to room temperature to obtain electronic conductor nanorod powder; 2. Preparation of polymer / inorganic salt composite fiber diaphragm with built-in electronic conductor nanorod filler: (1) dissolving the electronic conductor nanorod powder and raw material II in N,N-dimethylformamide, stirring for 2-3 hours to obtain a mixed solution II; dissolving the polymer I powder in the mixed solution II, heating and stirring for 6-8 hours to obtain an electrospinning solution II; the raw material II is one or more of zinc acetate, zinc nitrate, copper acetate or copper nitrate; the polymer I is one or more of polyimide or polyamic acid; (2) extracting the electrospinning solution II into a 5 mL syringe, adjusting the distance between the receiver and the metal needle of the syringe to 10-20 cm, the DC voltage to 12-18 kV, and the injection speed to 0.5-1.0 mL / h, and performing electrospinning to obtain a polymer / inorganic salt composite fiber diaphragm with built-in electronic conductor nanorod filler; 3. Preparation of polymer / metal oxide / metal nitride composite fiber diaphragm with built-in electronic conductor nanorod filler: The polymer / inorganic salt composite fiber diaphragm with built-in electronic conductor nanorod filler is placed in a box-type muffle furnace, heated to 250°C at a heating rate of 2-3°C / min, and kept at a temperature for 1-2 hours. The temperature is then further heated to 340°C at a heating rate of 2-3°C / min, and kept at a temperature for 1-2 hours. The membrane is then naturally cooled to room temperature to obtain a polymer / metal oxide / metal nitride composite fiber diaphragm with built-in electronic conductor nanorod filler.

2. The method for preparing a fiber diaphragm according to claim 1, characterized in that: In step one (1), the mass ratio of raw material I to N,N-dimethylformamide in the electrospinning solution I is 1:(6-6.5).

3. The method for preparing a fiber diaphragm according to claim 1, characterized in that: In step one (1), the mass ratio of polyvinyl pyrrolidone to N,N-dimethylformamide in the electrospinning solution I is 1:(6.5-7).

4. The method for preparing a fiber diaphragm according to claim 1 or 2, characterized in that: In step 2 (1), the mass ratio of the electronic conductor nanorod powder to N,N-dimethylformamide in the electrospinning solution II is 1:(22-72).

5. The method for preparing a fiber diaphragm according to claim 1 or 2, characterized in that: In step 2 (1), in step 2 (1), the mass ratio of the electronic conductor nanorod powder to the polymer I powder in the electrospinning solution II is 1: (6.7-20).

Citation Information

Patent Citations

  • Method for preparing polyimide porous nanofiber electrode diaphragm

    CN104752665A

  • Fiber diaphragm, preparation method thereof and application of fiber diaphragm in in-situ polymerization solid-state lithium battery

    CN117594951A

  • Separator for electrochemical device, method for manufacturing the same, electrochemical device including the same

    KR1020180072115A